Calculation and experimental studies of the technology of heating steel billets in pusher furnaces - V. I. Timoshpolsk; I. A. Trusova; E. O. Tskitishvili; P. A. Laktionov; N. A. Kiyashko (Литьë и металлургия, 2000)
The article gives analytical solution to the problem of nonsymmetric heating of blooms in continuous furnaces based on the '‘equivalent sources method’'. Parametrical identification by the results of industrial experiments has shown sufficient accuracy and reliability of the method.